Implementation of Ergonomics Approach in Sociology Learning to Decrease Physiological Disorders of Student Online Learning - Ferdinand Kerebungu; I Wayan Gede Suarjana; Siti Fathimah (Yayasan Keluarga Guru Mandiri, 2022)
Online learning activities carried out by students spend several hours a day in front of computers and smartphones. If the activities in this learning are not aligned with the ergonomic approach in each student's activity, of course, it will cause subjective fatigue experienced by students. This study aims to determine the influence of the implementation of the ergonomic approach on sociology learning on the decrease in physiological disorders assessed from subjective fatigue in high school students, especially in class XI. This research is an experimental study with treatment by subject design. The target population in this study was all students enrolled in SMAN 3 Tondano, while the affordable population was students who received sociology subjects. The research sample was 30 students. The research instrument used was a questionnaire of 30 items of rating scale to assess subjective fatigue. Data analysis used through descriptive tests, data normality tests, and T-tests using SPSS 25 for IOS analysis. The results showed that the difference in the average subjective fatigue before the learning process between the control period and the experimental period was 0,40 or the difference only reached 1,27%. The difference in the average subjective fatigue after the learning process between the control and experimental periods is 31,44, or the difference reached 37.36%. The results of the different tests showed a meaningful difference (p0.05). The difference in subjective fatigue reduction between the control and experimental periods reached 31.04 (62.18%). Therefore, it can be concluded that implementing an ergonomic approach to sociology learning can reduce subjective complaints in the learning process so that students avoid health problems and physiological disorders in the form of physical fatigue.